Acetylcholine precursor, citicoline (cytidine 5′‐diphosphocholine), reduces hypoglycaemia‐induced neuronal death in rats. (14th January 2018) - Kim, J. H.; Choi, B. Y.; Kho, A. R.; Lee, S. H.; Jeong, J. H.; Hong, D. K.; Lee, S. H.; Sohn, M.; Ryu, O. H.; Choi, M.‐G.; Suh, S. W.
Abstract : Citicoline (cytidine 5′‐diphosphocholine) is an important precursor for the synthesis of neuronal plasma membrane phospholipids, mainly phosphatidylcholine. The administration of citicoline serves as a choline donor for the synthesis of acetylcholine. Citicoline has been shown to reduce the neuronal injury in animal models with cerebral ischaemia and in clinical trials of stroke patients. Citicoline is currently being investigated in a multicentre clinical trial. However, citicoline has not yet been examined the context of hypoglycaemia‐induced neuronal death. To clarify the therapeutic impact of citicoline in hypoglycaemia‐induced neuronal death, we used a rat model with insulin‐induced hypoglycaemia. Acute hypoglycaemia was induced by i.p. injection of regular insulin (10 U kg ‐1 ) after overnight fasting, after which iso‐electricity was maintained for 30 minutes. Citicoline injections (500 mg/kg, i.p.) were started immediately after glucose reperfusion. We found that post‐treatment of citicoline resulted in significantly reduced neuronal death, oxidative injury and microglial activation in the hippocampus compared to vehicle‐treated control groups at 7 days after induced hypoglycaemia. Citicoline administration after hypoglycaemia decreased immunoglobulin leakage via blood‐brain barrier disruption in the hippocampus compared to the vehicle group. Citicoline increased choline acetyltransferase expression for phosphatidylcholine synthesis after hypoglycaemia. Altogether, the present findings suggest that neuronal membrane stabilisation by citicoline administration can save neurones from the degeneration process after hypoglycaemia, as seen in several studies of ischaemia. Therefore, the results suggest that citicoline may have therapeutic potential to reduce hypoglycaemia‐induced neuronal death.